Respostas

2014-07-10T10:23:36-03:00
Se (x-y)² - (x+y)² = -20 então x.y é igual a:

(x-y)²        -   (x+y)²
(x-y)(x-y)       -    (x+y)(x+y) = - 20   fazer a distributiva
(x² -xy-xy + y²)  -(x² +xy+xy+y²) = - 20
x² -2xy + y²    -    (x² + 2xy + y²) = - 20   arrumar o sinais
x² - 2xy + y²  - x² - 2xy - y²  = - 20   -------------------------------arrumar a casa

x² - x² + y² - y² -2xy - 2xy = - 20
   0           0     - 4xy = - 20

-4xy = - 20
xy = - 20/-4
xy = + 20/4


então x.y é igual a:  5

1 5 1